Potret Kesadaran Masyarakat Dalam Mengelola Sampah Rumah Tangga - Lia Aulia; Muhammad Rofiq setiawan; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to understand the extent to which the Sentiong community cares about managing household waste. The method used is descriptive qualitative using data collection techniques carried out through investigations and interviews. The results of the research imply that the awareness of the Sentiong community in dominating household waste is still in the small category. This is due to the large amount of waste being thrown away haphazardly, the lack of waste sorting, and the lack of public knowledge. Throwing away rubbish is a daily activity that everyone does, this can lead to deviant behavior if it is carried out by people who behave badly towards the environment. Waste can cause problems, but it can also strengthen the economic life of the community. Various types of waste produced from industry and households, if not managed well and correctly, will have the potential to weaken the community's economy, this is because it will absorb quite a large amount of funds for handling waste that is not managed well and correctly, which is considered from a hygiene, health and environmental perspective.